A study of the compactness of wave functions based on Shannon entropy indices : A seniority number approach - Lain, Luis (2015)
This work reports the formulation of Shannon entropy indices in terms of seniority numbers of the Slater determinants expanding an N-electron wave function. Numerical determinations of those indices prove that they provide a suitable quantitative procedure to evaluate compactness of wave functions and to describe their configurational structures. An analysis of the results, calculated for full configuration interaction wave functions in selected atomic and molecular systems, allows one to compare and to discuss the behavior of several types of molecular orbital basis sets in order to achieve more compact wave function expansions, and to study their multiconfigurational character.